Trans-Boundary Water Governance: An Urgent Need of the Formulation of Pak-Afghan Trans-Border Water Governance Mechanism - Zahida Jabeen; Muhamad Riaz Shad; Jafar Nazir (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Trans-boundary watercourses drain larger parts and ensures the flow of fresh waters in different parts of the world. In trans-boundary watercourses, upper-riparians have an upper edge to deal with the water resources of the trans-border rivers while the lower-riparians have a compromising position. Kabul River Basin is one of the major trans-border water basins which drains the vast areas in Afghanistan and Pakistan. Recently, uneven weather patterns and climate change worldwide affected the national economies with an irreparable loss and created survival threat to human beings, and to other species. Pakistan is considered as one of the most vulnerable countries to face the impacts of the climate change. Dryness of fresh water resources is one of the impact of climate change that will ultimately affect the Kabul River along with other rivers of Pakistan. This study adopted qualitative research methodology by analyzing the secondary data to address the main research question which revolves around the adaptation of any formal water sharing mechanism between the two co-riparian countries. The study concludes that Pakistan should initiate hydro-diplomacy with Afghanistan, and enter into a formal bilateral trans-border water sharing treaty under the guidelines of the UN Convention 1997.